Islamic and Western Education Systems – Perceptions of Selected Educationists in Malaysia (Journal of Education and Educational Development, 2020)
This research article explores the perceptions of Muslim educationists in Malaysia about the Islamic and the western education systems. Views of two faculty members, who are active proponents of Islamic education, were acquired through interviews and their perceptions on Islamic and western education systems were analyzed and then contrasted against the views of Dr. Syed Naquib al-Attas, who is considered to be one of the architectsof the project of Islamization of knowledge and education.Qualitative exploratory methodology was followed for this research, where the views of the two educationists were analyzed using thematic analysis,and the views of Dr. Naquib al-Attas were derived through document analysis of his writings on education and finally contrasted.It was revealed that there exists a gap in the understanding of the depth of philosophical concepts and issues of education between these educationists and Naquib al- Attas.